2017
DOI: 10.1177/1756287217701391
|View full text |Cite
|
Sign up to set email alerts
|

An update on best practice in the diagnosis and management of post-prostatectomy anastomotic strictures

Abstract: Postprostatectomy vesicourethral anastomotic stenosis (VUAS) remains a challenging problem for both patient and urologist. Improved surgical techniques and perioperative identification and treatment of risk factors has led to a decline over the last several decades. High-level evidence to guide management is lacking, primarily relying on small retrospective studies and expert opinion. Endourologic therapies, including dilation and transurethral incision or resection with or without adjunct injection of scar mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 78 publications
0
15
2
1
Order By: Relevance
“…There are few reported comparisons of stenosis formation after RRP and RALP. We found 3.6% stenosis after RRP and 1.3% after RALP, both in the lower range of previously reported incidences from studies on RRP of 2.7-15% [5,13,[20][21][22] and RALP 1.1-3.8% [8,9,14,15,23,24]. In a study in 2012, Wang et al [12] showed a stenosis incidence of 7.5% after RRP (n = 707) and 2.1% after RALP (n = 1038).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…There are few reported comparisons of stenosis formation after RRP and RALP. We found 3.6% stenosis after RRP and 1.3% after RALP, both in the lower range of previously reported incidences from studies on RRP of 2.7-15% [5,13,[20][21][22] and RALP 1.1-3.8% [8,9,14,15,23,24]. In a study in 2012, Wang et al [12] showed a stenosis incidence of 7.5% after RRP (n = 707) and 2.1% after RALP (n = 1038).…”
Section: Discussioncontrasting
confidence: 44%
“…Stenosis may lead to additional surgery and a risk of future incontinence [10,11]. The exact aetiology of stenosis formation is largely unknown, but proposed risk factors include age, elevated body mass index (BMI), smoking, anastomotic suture technique, anastomotic urinary leakage, and excessive blood loss [12,13]. There are few studies comparing the risk of stenosis after open and robot-assisted radical prostatectomy, most hampered by small size, few observations of stenosis, and/or a nonrandomised design [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the only study in this review involving a pure RARP cohort reported a low rate of BOO at 12 months of only 3% 10 . Conversely, radiotherapy following prostatectomy can cause obliterative endarteritis, tissue necrosis and fibrosis, resulting in VUAS or urethral stricture 41,42 . In a small series of men treated with salvage radiotherapy following RP, a high rate of BOO (43.8%) was found following both treatments 17 …”
Section: Discussionmentioning
confidence: 86%
“…La de origen traumático, se presenta hasta en el 3%-25% de las fracturas de pelvis y está relacionado con la caída a horcajadas y la fractura de Malgaigne. La de origen iatrogénico 16 hasta en un 41% de veces es secundario a procedimientos endourológicos que cada vez son más frecuentes como la resección transuretral de próstata o secundario a radiación. 17 En el caso de este estudio, el 61% fue origen traumático y el 39% de origen iatrogénico, porcentajes que con el paso del tiempo tienden a ser más homogéneos.…”
Section: Discussionunclassified